2022
DOI: 10.12659/ajcr.937318
|View full text |Cite
|
Sign up to set email alerts
|

A 66-Year-Old Woman with Achondroplasia and Quadriparesis with an Ovarian Cyst Erroneously Diagnosed as Urinary Retention by an Automated Bladder Scan

Abstract: Patient: Female, 66-year-old Final Diagnosis: Ovarian cyst Symptoms: Urinary retention Medication: — Clinical Procedure: Automatic bladder scan Specialty: Genetics • Geriatrics • General and Internal Medicine • Obstetrics and Gynecology • Radiology • Urology Objective: Mistake in diagnosis Background: Automated bladder scanning has become a principal tool in the assessment and management of chronica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Reports showed that ovarian tumors caused UR, 3 and an ovarian cyst was misdiagnosed as UR. 4 However, to my knowledge, there is no English report of marked UR misleading gynecologists. The etiology of her UR remains unclear.…”
mentioning
confidence: 94%
“…Reports showed that ovarian tumors caused UR, 3 and an ovarian cyst was misdiagnosed as UR. 4 However, to my knowledge, there is no English report of marked UR misleading gynecologists. The etiology of her UR remains unclear.…”
mentioning
confidence: 94%